2017
DOI: 10.1186/s12917-017-1260-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intramuscularly administered enrofloxacin on the susceptibility of commensal intestinal Escherichia coli in pigs (sus scrofa domestica)

Abstract: BackgroundIn the European Union, various fluoroquinolones are authorised for the treatment of food producing animals. Each administration poses an increased risk of development and spread of antimicrobial resistance. The aim of this study was to investigate the impact of parenteral administration of enrofloxacin on the prevalence of enrofloxacin and ciprofloxacin susceptibilities in the commensal intestinal E. coli population.Methods E. coli isolates from faeces of twelve healthy pigs were included. Six pigs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 49 publications
5
25
0
Order By: Relevance
“…Taking into account these limitations, the presented results still indicate a significant impact of ENR on the fecal microbiota. Two studies using a similar methodology [13,14] (i.e. plating of pig fecal material on a selective agar base to enumerate E. coli from the microbiota) demonstrated a similar susceptibility shift for E. coli from the fecal microbiota after treatment with ENR.…”
Section: Bacteriologymentioning
confidence: 90%
See 1 more Smart Citation
“…Taking into account these limitations, the presented results still indicate a significant impact of ENR on the fecal microbiota. Two studies using a similar methodology [13,14] (i.e. plating of pig fecal material on a selective agar base to enumerate E. coli from the microbiota) demonstrated a similar susceptibility shift for E. coli from the fecal microbiota after treatment with ENR.…”
Section: Bacteriologymentioning
confidence: 90%
“…Previously, it has been demonstrated that the FQ antimicrobials have a detrimental effect on the Gram-negative aerobic microbiota [ 12 ]. Römer et al demonstrated that parenteral administration of ENR in piglets caused a considerable reduction of the susceptible intestinal E. coli population, in favor of resistant E. coli isolates [ 13 ]. Wiuff et al also demonstrated a rapid development of resistance in coliforms in the gut of pigs after PO or IM administration of ENR [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are comparable to results recently published from the EFFORT consortium (27), but varying from results of a previous study, where a lower AMU quantification of HPCIAs for pigs in Switzerland based on total amount of given active ingredient was observed (33). Due to the documented spread of resistance genes e.g., against fluoroquinolones in the pig sector (34), every use of these substances should be of concern and further research investigating restriction of indications and potential reductions in usage is needed.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the half-life of FQ in pigs is short. 2,23 While some studies show a duration of an increased excretion of antimi crobial resistant germs for three to four weeks after treatment, 10,22,29 or no increased excretion of fluoroquinolone-resistant E. coli after treating pigs with FQ , 7 other authors isolated FQ resistant E coli up to eight weeks after treatment with FQ 26 and some data indicates that all antimicrobial therapies over the entire life are relevant, not only those carried out shortly before sampling. 1 The most frequent indication for the use of antibiotics in sows in Switzerland is PDS, 16 which usually occurs shortly after farrowing.…”
Section: Discussionmentioning
confidence: 99%
“…17,21 A shift in susceptibility of commensal E. coli towards resistance could be shown in pigs intramusculary treated with fluoroquionolones and in untreated penmates. 26 In the case of oral therapy with pharmaceutical premixes, surrounding bacterial flora come into direct contact with residues of active substances in dust and feed in the barn. 14 Certain active substances, such as tetracyclines or fluoroquinolones, undergo limited metabolization in pigs and are thus effectively excreted.…”
Section: Introductionmentioning
confidence: 99%